Reporting the Validity of Evidence-Based Librarianship Instrument in Electronic Resources Acquisition Decision - Mustafa, A’dillah; Abdullah, Noorhidawati (2017)
In determining the acquisition decision of the electronic resources, librarians currently looking for a holistic approach in their decision making. Librarians believed that Evidence–based Librarianship (EBL) practice is a comprehensive and practical approach that utilizing the best available evidence in library acquisition making. This paper aims to reports the validity of the instrument developed through adopt and adapt methods. Basically, the instrument represents five dimensions of the framework. The instrument was designed to tab the types of evidence used by librarians in their decision. This instrument only focused on the acquisition of electronic resources. The validity analysis is reported using two methods: Content Validity Index (CVI) and Scale level Content Validity Index (S-CVI). The validity analysis also calculated the Scale level Content Validity Index Average (S-CVI/Ave) which score of 0.94 consider as achieved high-level agreement and acceptable. The validation procedures are also described in the report. Overall, this instrument has achieved a good content validity.